2013
DOI: 10.3109/13880209.2013.805790
|View full text |Cite
|
Sign up to set email alerts
|

HPLC method with fluorescence detection for the determination of ligustilide in rat plasma and its pharmacokinetics

Abstract: Context: Few methods have been reported for the quantification of ligustilide (LIG) in biosamples: the pretreatment of the biological samples were laborious and time-consuming. Objective: A high-performance liquid chromatographic method with fluorescence detection (HPLC-FLD) for the determination of LIG in rat plasma was developed and validated. Pharmacokinetics and bioavailability of LIG were determined by systematic investigation in Sprague-Dawley rats. Materials and methods: LIG was isolated from the volati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…In this study, we found that the plasma concentrations of the active ingredients of the ATX extracts, namely Z-ligustilide, n-butylidenephthalide, chlorogenic acid, and ferulic acid, were below the detection limit after 24 h of the oral administration in mice. The low concentration of the ingredients may be attributed, at least in part, to their short biological half-lives (i.e., [the half-life determined in rats] Z-ligustilide, 3.02-6.90 h [33]; n-butylidenephthalide, 3.54 h [34]; chlorogenic acid, 1.70 h [35]; ferulic acid, 0.618-0.885 h [36]). In addition to the rapid disappearance, the lack of proper exposure (i.e., low oral bioavailability) may be contributed to the difficulty in the detection.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that the plasma concentrations of the active ingredients of the ATX extracts, namely Z-ligustilide, n-butylidenephthalide, chlorogenic acid, and ferulic acid, were below the detection limit after 24 h of the oral administration in mice. The low concentration of the ingredients may be attributed, at least in part, to their short biological half-lives (i.e., [the half-life determined in rats] Z-ligustilide, 3.02-6.90 h [33]; n-butylidenephthalide, 3.54 h [34]; chlorogenic acid, 1.70 h [35]; ferulic acid, 0.618-0.885 h [36]). In addition to the rapid disappearance, the lack of proper exposure (i.e., low oral bioavailability) may be contributed to the difficulty in the detection.…”
Section: Discussionmentioning
confidence: 99%
“…Glucuronic acid and sulfuric acid conjugates of rhein are dominant in urine and fecal excreta. Only 20% of the prototype rhein is excreted in urine and feces (Wan et al, 2013).…”
Section: Excretion Excretion Routes and Formmentioning
confidence: 99%
“…Traditionally, ASR can be distinguished by experienced Danggui farmers [12], but this method is obviously dependent on highly subjective judgments and lacks of universality. On the other hand, thin layer chromatography, HPLC, CE-DAD, GC-MS, LC-MS analytical methods are used to discriminate ASR [13][14][15][16][17]. Although these methods have made significant contributions to the progress of quality control of ASR, however, they cannot effectively distinguish the geographic origin of ASR due to insufficient compound information.…”
Section: Introductionmentioning
confidence: 99%